Development of combined vector and torque control methods for independent two induction motor drives - Hairul Nizam, Talib; Zulkifilie, Ibrahim; N. A. , Rahim; N. M., Yaakob (2012)
Many applications use two or more motors operating in parallel configuration by using one variable speed drive. This system is able to control these multiple motors at the same desired motor speed operation which provide advantages in terms of components and cost reduction. However, the system is not able to control each motor separately if it is desired to operate at different speeds and it also cannot withstand the load disturbance. To address this problem, the design of combined Vector Control-Direct Torque Control (DTC) methods is proposed and their performance is investigated for the case of independent controlled two induction motors fed by single Five Leg Inverter (FLI) method. Double Zero Sequence (DZS) Injection Method Space Vector Pulse Width Modulation (SVPWM) scheme is used for the FLI. Simulation results from the Simulink/Matlab that verify the validity of the method are also included. The results show the ability of the proposed method to control motor speed independently under forward-reverse step speed command and load disturbance condition.